Comparison of visual and acoustic surveys for the detection and dynamic management of North Atlantic right whales (Eubalaena glacialis) in Canada. Issue 2 (27th December 2022) - Ceballos, Valentina; Taggart, Christopher; Johnson, Hansen
Abstract: The goal of this study was to develop a simulation to quantitatively compare acoustic and visual surveys and use it to inform current and future North Atlantic right whale ( Eubalaena glacialis ) risk mitigation. We expanded upon an established whale movement model, incorporating realistic right whale cues for visual and acoustic detection within dynamic management zones in the Gulf of Saint Lawrence, Canada. Survey transits by acoustic (Slocum gliders) and visual (aircraft, vessels, and Remotely Piloted Aircraft Systems) platforms were simulated using representative platform movements and detection functions. We used a Monte Carlo approach to estimate the probability of detecting a cue, in each zone, as a function of survey platform, number of right whales, and survey transits. Acoustic gliders detected right whale presence in every scenario. Single transits of a management zone by visual surveys were only able to reliably (>0.5 probability) detect right whales when more than 20 whales were present. Twenty or more transits were required to reliably detect a single right whale. Our results serve as a tool to be used by decision‐makers to inform optimal right whale monitoring strategies that consider the relative strengths of the various platforms. Abstract : We developed a simulation to compare acoustic and visual surveys to inform North Atlantic right whale risk mitigation. We expanded upon an established whale movement model by incorporating cues for visual and acoustic detection within dynamic management zones in the Gulf of Saint Lawrence, Canada and survey transits with representative platform movements and detection functions. The probability of detecting a cue as a function of zone, survey platform, number of whales, and survey transits revealed that acoustic gliders detect whale presence in every scenario, but visual surveys can only reliably detect whales with many transits or when many whales are present.